Analisis Nilai-nilai karakter dalam animasi riko the series sebagai alternatif pembelajaran karakter - Yuniati, Nurul Izzah Dwi; Chudari, Ima Ni'mah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Character education is not only providing knowledge to children about what is right and wrong. More importantly, character education is the cultivation of habits (habits) that are following the expectations of the environment around students so that they can act properly. This study aims to describe the character values contained in the animation Riko The Series and describe the realization of the character values contained in the animation. This study uses qualitative research methods and uses content analysis it. The research data used is Riko The Series animation, ten-line production. The animation is carefully observed to analyze the value of the contained characters later. The benchmark used in the data reduction process is based on the character value of the Ministry of Education. There are 18 character values set by the Ministry of Education and Culture, namely religion, honesty, tolerance, discipline, perseverance, innovation, independence, democracy, curiosity, national spirit, love for the homeland, respect for achievement, and friendship/communication, love of peace, love to read, love the environment, social care and a sense of responsibility. The results of this study are Riko The Series animation can be used as an example for elementary school-age children, especially the importance of curiosity, faith/religion, and honesty under the guidance of teachers and parents likes to read, loves the environment around, and cares for others and a sense of responsibility.